2021
DOI: 10.1111/jonm.13387
|View full text |Cite
|
Sign up to set email alerts
|

Effect of workplace fun on Chinese nurse innovative behaviour: The intermediary function of affective commitment

Abstract: Aim To assess the effects of workplace fun on nurse innovative behaviour and to confirm the intermediary function of affective commitment. Background Employee innovative behaviour has a crucial function in survival and development of an organisation. On the basis of the theory of social exchange, there has been inadequate study of the influence of workplace fun on nurse innovative behaviour mediated by affective commitment. Methods A cross‐sectional, descriptive correlational research design was conducted for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…This is because culture is commonly found to be key in supporting, encouraging, and fostering employees' IIB at work [7,53]. Nonetheless, scholars in health services research have called for further studies to extend our current understanding of the multifaceted concept of organizational culture and its role in encouraging individual innovation at work [1,4,[54][55][56][57]. For example, in examining 331 Chinese nurses, Jing et al [56] found that organizational culture, studied as workplace fun, was positively correlated with IIB.…”
Section: Internal Market-oriented Cultures (Imocs)mentioning
confidence: 99%
See 1 more Smart Citation
“…This is because culture is commonly found to be key in supporting, encouraging, and fostering employees' IIB at work [7,53]. Nonetheless, scholars in health services research have called for further studies to extend our current understanding of the multifaceted concept of organizational culture and its role in encouraging individual innovation at work [1,4,[54][55][56][57]. For example, in examining 331 Chinese nurses, Jing et al [56] found that organizational culture, studied as workplace fun, was positively correlated with IIB.…”
Section: Internal Market-oriented Cultures (Imocs)mentioning
confidence: 99%
“…Nonetheless, scholars in health services research have called for further studies to extend our current understanding of the multifaceted concept of organizational culture and its role in encouraging individual innovation at work [1,4,[54][55][56][57]. For example, in examining 331 Chinese nurses, Jing et al [56] found that organizational culture, studied as workplace fun, was positively correlated with IIB. As such, this study has focused on a specific type of organizational culture attentive to employees, namely IMOC.…”
Section: Internal Market-oriented Cultures (Imocs)mentioning
confidence: 99%
“…Similarly, various predictors and consequences of affective commitment are shown in Table 1. Based on this, we speculate that affective commitment is the best to explain the association between perceived equality and contextual performance as ensuring equity to the diverse workforce will have an effect on their emotional responses (e.g., affective commitment) [52][53][54][55][56][57][58][59][60][61][62][63], further affecting their behavioral outcomes (e.g., contextual performance) [64][65][66][67][68]. us, extending on prior studies, we hypothesize that when employees perceive equality in diversity practice, their affective commitment gets affected, which further has implications on their contextual performance (H 3 ).…”
Section: Perceived Equality Organizational Commitment Andmentioning
confidence: 99%
“…With the continuous advancement of nursing reform and development, management innovation, technology innovation and service innovation have become inevitable trends in the development of nursing work (Wang et al, 2021). In clinical nursing work, nurses are motivated to engage in innovative practices through the use of innovative products, services, technologies and methods primarily to seek to improve patient experiences, health outcomes and nursing practice (Jing et al, 2021). Obviously, encouraging innovation behaviours among nurses is already an important development direction for health care scholars (ICN, 2009).…”
Section: Introductionmentioning
confidence: 99%